Productive Waqf in Sustainable Development (SDGs): An Interdisciplinary Analysis of Islamic Law and the Global Agenda - Ilyan Nurul Azam; Zainol Fata; Abdul Hamid Bhustomi Nur (Ta'amul: Journal of Islamic Economics, 2025)
Productive waqf represents a strategic Islamic economic instrument rooted in the principles of justice, equity, and social solidarity. However, its contemporary implementation often remains limited to symbolic and consumptive uses. This article explores the potential of productive waqf to contribute to the Sustainable Development Goals (SDGs) by employing an interdisciplinary approach that bridges Islamic legal thought (fiqh) and development studies. Utilizing the framework of maqashid al-shariah (the objectives of Islamic law), the study identifies conceptual parallels between Islamic social finance and global development priorities. The analysis reveals that productive waqf can serve as an ethical and transformative alternative to both global capitalism and religious extremism by promoting inclusive economic empowerment and equitable asset redistribution. The article concludes by advocating for the reinterpretation of Islamic legal discourse and the institutional reform of waqf governance to align with the goals of sustainable and just development